Increased frequency of the rs2066853 variant of aryl hydrocarbon receptor gene in patients with acromegaly1. (17th March 2014) - Cannavo, S.; Ferrau, F.; Ragonese, M.; Romeo, P. D.; Torre, M. L.; Puglisi, S.; De Menis, E.; Arnaldi, G.; Salpietro, C.; Cotta, O. R.; Albani, A.; Ruggeri, R. M.; et al.
Summary Context Aryl hydrocarbon receptor (AHR) pathway has a key role in cellular detoxification mechanisms and seems implicated in tumorigenesis. Moreover, polymorphisms and mutations of AHR gene have been associated with several human and animal tumours. Although AHR has been found differently expressed in pituitary adenomas, AHR gene mutation status has never been investigated in acromegalic patients. Design In this study, we evaluated patients with apparently sporadic GH‐secreting pituitary adenoma for AHR gene variants. Patients and Methods Seventy patients with sporadic GH‐secreting pituitary adenoma (M = 27, age 59·1 ± 1·6 years) and 157 sex‐ and age‐matched controls were enrolled in the study. In all patients and controls, the exons 1, 2, 3, 5 and 10 of AHR gene were evaluated for nucleotide variants by sequencing analysis. Results The rs2066853 polymorphism was identified in the exon 10 of 18/70 acromegalic patients and 9/157 healthy subjects (25·7 vs. 5·7%, χ2 = 18·98 P < 0·0001), in homozygosis in one patient and in heterozygosis in the other 17 and in the 9 healthy subjects. Moreover, a heterozygous rs4986826 variant in exon 10 was identified in a patient with heterozygous rs2066853 polymorphism, and in the patient with homozygous rs2066853 variant. This second polymorphism was not detected in the control group. Patients with rs2066853 polymorphism showed increased IGF‐1 ULN (P < 0·05) and prevalence of cavernous sinus invasion (P = 0·05), thyroid (P = 0·02), bladder (P = 0·0001) or lymphohematopoietic (P < 0·05) tumours. Conclusions AHR gene rs2066853 polymorphism is significantly more frequent in acromegalic patients than in healthy subjects and is associated with increased disease aggressivity. Moreover, the rs4986826 variant was detected in few patients with rs2066853 polymorphism, but its role is to be cleared.